2018
DOI: 10.2147/copd.s183740
|View full text |Cite
|
Sign up to set email alerts
|

Strain measurement on four-dimensional dynamic-ventilation CT: quantitative analysis of abnormal respiratory deformation of the lung in COPD

Abstract: PurposeStrain measurement is frequently used to assess myocardial motion in cardiac imaging. This study aimed to apply strain measurement to pulmonary motion observed by four-dimensional dynamic-ventilation computed tomography (CT) and to clarify motion abnormality in COPD.Materials and methodsThirty-two smokers, including ten with COPD, underwent dynamic-ventilation CT during spontaneous breathing. CT data were continuously reconstructed every 0.5 seconds. In the series of images obtained by dynamic-ventilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It was reported that normal deformation of the lung would appear at lung areas with large respiratory movements, such as the lung base and the dorsal part of the lung, and abnormal deformation is observed throughout the lung caused by heterogeneous ventilation or partial airtrapping due to emphysema and airway disease of COPD. 9 These observations suggest that abnormal pulmonary deformation by ventilation can be observed in COPD patients who smoked heavily and this differentiates them from asthma patients. Hida et al reported the maximal diaphragmatic motion in severe COPD patients during forced breathing was smaller compared to normal subjects.…”
Section: Discussionmentioning
confidence: 89%
“…It was reported that normal deformation of the lung would appear at lung areas with large respiratory movements, such as the lung base and the dorsal part of the lung, and abnormal deformation is observed throughout the lung caused by heterogeneous ventilation or partial airtrapping due to emphysema and airway disease of COPD. 9 These observations suggest that abnormal pulmonary deformation by ventilation can be observed in COPD patients who smoked heavily and this differentiates them from asthma patients. Hida et al reported the maximal diaphragmatic motion in severe COPD patients during forced breathing was smaller compared to normal subjects.…”
Section: Discussionmentioning
confidence: 89%
“…Our study added to the growing body of evidence supporting the utility of strain measurement in quantitative analysis of COPD. 17 …”
Section: Discussionmentioning
confidence: 99%
“… 16–18 Mathematically speaking, strain on a point of a deformable body is determined from the derivatives of the displacement field that deforms the body. 19–23 Xu et al 17 have firstly introduced strain analysis in COPD to monitor pulmonary motion during ventilation. Although that study demonstrated the potential of strain measurement for evaluating pulmonary mechanics, only the “middle” field of the lung were analyzed with single strain-related parameter (maximum principal strain).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that AT heterogeneity on full-expiration better reflects pulmonary function than emphysema heterogeneity on full-inspiration, which is rarely reported in the literature. A more heterogeneous distribution of emphysema and/or AT corresponds to relatively more residual normal lung parenchyma, better synchronization of respiratory movements that can be quantitatively assessed by strain measurement using dynamic-ventilation CT, and better pulmonary function 17,18. In the early stage of small airway lesions, expiratory dysfunction manifests exclusively, while with the progression of disease, both inspiratory and expiratory functions show impairment.…”
Section: Discussionmentioning
confidence: 99%